Legal Protection Of Persons With Disabilities In Education - Ary Dwi Kurniawan; Imam Budi Santoso; Pri Pambudi Teguh (IHSA Institute, 2021)
Protection and guarantee of human rights are not only necessary for normal citizens but also for persons with disabilities, namely people who have physical, mental, intellectual, or sensory limitations. In reality, there are still many people with disabilities who are discriminated against in relation to the fulfillment of the right to education, employment, public facilities such as transportation, places of worship, places of entertainment, and equality before the law. The problem of this research is how are the efforts of the Karawang Regency government in fulfilling the rights of persons with disabilities in the field of education? What is the policy for educators to educate people with disabilities? Are there any differences that the Karawang Regency government applies in fulfilling the rights of persons with disabilities and children with special needs?